Single-Molecule RNA Sequencing Reveals IFNγ-Induced Differential Expression of Immune Escape Genes in Merkel Cell Polyomavirus–Positive MCC Cell Lines - Sauerer, Tatjana; Lischer, Christopher; Weich, Adrian; Berking, Carola; Vera, Julio; Dörrie, Jan (Frontiers in Microbiology, 2021)
Merkel cell carcinoma (MCC) is a rare and highly aggressive cancer, which is mainly caused by genomic integration of the Merkel cell polyomavirus and subsequent expression of a truncated form of its large T antigen. The resulting primary tumor is known to be immunogenic and under constant pressure to escape immune surveillance. Since IFNɣ, a key player of immune response, is secreted by many immune effector cells and has been shown to exert both anti-tumoral and pro-tumoral effects, we studied the transcriptomic response of MCC cells to IFNɣ. Especially immune modulatory effects that may help the tumor evade immune surveillance were of high interest to our investigation. The effect of IFNɣ treatment on the transcriptomic program of three MCC cell lines (WaGA, MKL-1, and MKL-2) was analyzed using single molecule sequencing via the Oxford Nanopore platform. A significant differential expression of several genes was detected across all three cell lines. Subsequent pathway analysis and manual annotation showed a clear up-regulation of genes involved in the tumor’s immune escape due to IFNɣ treatment. The analysis of selected genes on protein level underlined our sequencing results. These findings contribute to a better understanding of immune escape of MCC and may help in clinical treatment of MCC patients. Further we demonstrate that single molecule sequencing can be used to assess characteristics of large eukaryotic transcriptomes and thus contribute to a broader access to sequencing data in the community due to its low cost of entry.